Perjanjian Baru dalam Perspektif Historis dan Teologis: Latar Belakang, Penulisan, dan Pesan Utamanya - Fadlian Lontoh (International Forum of Researchers and Lecturers, 2025)
The New Testament is an essential part of the Christian Bible, containing testimonies concerning the life, ministry, death, and resurrection of Jesus Christ, as well as the development of the early Church. To fully understand its message, it is necessary to examine the historical and theological contexts that shaped its composition. This article aims to explore the New Testament from historical and theological perspectives by examining the social, political, cultural, and religious background of the first-century world, the process of the writing of the New Testament books, and their principal theological messages. The study employs a library research method with a descriptive-analytical approach to various biblical and theological sources. The findings indicate that the New Testament emerged within the context of Roman rule, Jewish religious traditions, and Hellenistic cultural influences, all of which shaped both the authors and their audiences. The books of the New Testament were written to address the needs of early Christian communities, affirm the identity of Jesus Christ, strengthen believers' faith, and provide guidance for Christian living. Theologically, the New Testament emphasizes central themes such as the Kingdom of God, salvation through Jesus Christ, grace, the formation of the Church, and eschatological hope. Therefore, an understanding of the historical background and theological message of the New Testament is essential for accurate interpretation and for maintaining its relevance to the life of the Church and contemporary Christian believers.